Induction of Parametric Design Vocabularies for Achieving Architectural Design Features إستنباط مفردات التصميم البارامتري لتحقيق مستهدفات التصميم المعماري - Eslam H M Kamel; Magdy M Radwan; Amr S Hassan (JES: Journal of Engineering Sciences, 2022)
Parametric design is called many meanings, including boundary design, modelling, standard design or variable design all lead to parametric meaning. Parameter design is an architectural approach that uses vocabulary in the light of a set of rules and design patterns that achieve design objectives in the presence of a design idea And research finds that the problem is that such a contemporary approach to design is rarely used in Egypt, although it is widely used around the world and in countries that share with Egypt the cultural heritage, nature and environmental condition, But the complexity of using programming techniques in design without studying or knowing the vocabulary on which the parameter and the associated formation rules depend directly affects design thinking and, in turn, affects the cost because it needs various and modern implementation techniques.. Therefore, the research aims to derive the vocabulary of the parametric approach and to identify the rules and patterns of this contemporary design approach. The paper addresses the different concepts of parameter design, the main principles on which it relies and the basic patterns on which the architect can identify the features of the parameter building. The study found that the parametric approach has been proven to be efficient using various modes of formation and various architectural vocabulary in achieving all design objectives. The research recommends using the benchmark for architectural design equation in identifying and analyzing parametric buildings in light of patterns and rules to reach the parametric vocabulary to achieve different design Features. يُطلق علي التصميم البارامتري العديد من المعاني منها التصميم الحدودي والنمذجي والتصميم القياسي أو التصميم المتغير جميعها تؤدي إلي المعني الخاص بالبارامتري. ويعتبر التصميم البارامتري نهج تصميم معماري يستخدم المفردات في ضوء مجموعة من القواعد والأنماط التصميمية التي تحقق أهداف التصميم في وجود فکرة تصميمية، ويجد البحث أن المشکلة تتمثل في أن مثل هذا النهج المعاصر في التصميم يندر إستخدامه في مصر علي الرغم من إستخدامه بشکل کبير وعلي نطاق واسع حول العالم وفي دول تشترک مع مصر في الموروث الثقافي والطبيعة والحالة البيئية، ولکن التعقيد المصاحب لإستخدام تقنيات البرمجة في التصميم دون دراسة أومعرفة المفردات التي تعتمد عليها البارامترية وقواعد التشکيل المرتبطة يؤثر بشکل مباشر علي الفکر التصميمي وبدوره يؤثر علي التکلفة لإحتياجه إلي تقنيات تنفيذ متنوعة وحديثة. وعليه يهدف البحث إلي إستنباط المفردات التي يتعامل معها النهج البارامتري والتعرف علي القواعد والأنماط الخاصة بهذا النهج التصميمي المعاصر. حيث تتناول الورقة البحثية المفاهيم المختلفة للتصميم البارامتري، والمبادئ الرئيسية التي يعتمد عليها والأنماط الأساسية التي يستطع المعماري من خلال التعرف عليها الإستدلال علي ملامح المبني البارامتري. وتوصلت الدراسة إلي أن النهج البارامتري قد ثبتت کفائته بإستخدام مختلف طرق التشکيل ومختلف المفردات المعمارية في تحقيق جميع الأهداف التصميمية، ويوصي البحث بإستخدام مسطرة القياس لمعادلة التصميم المعماري في التعرف علي المباني البارامترية وتحليلها في ضوء الأنماط والقواعد للوصول إلي المفردات البارامترية لتحقيق مختلف المستهدفات التصميمية.